UTILIZING CRITICAL READING STRATEGIES IN TEACHING READING COMPREHENSION: A QUALITATIVE STUDY IN VOCATIONAL HIGH SCHOOL - Nurrahmah, Khalisha; Fauzi Miftakh; Nina Puspitaloka (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This research aims to explore the implementation of critical reading strategies in teaching reading comprehension and to investigate students' responses toward these strategies. The study was conducted in a vocational high school in Karawang, using a qualitative method with a case study design. Data were collected through classroom observation, semi-structured interviews, and reflective journals. The results revealed that critical reading strategies such as previewing, annotating, questioning, summarizing, and evaluating text validity were effectively integrated into the reading comprehension process. These strategies helped students engage more deeply with texts, improve analytical thinking, and foster reading interest. Students showed positive responses, indicating increased motivation, comprehension, and critical awareness. However, some challenges were also found, including vocabulary limitations and cognitive overload. The study concludes that critical reading strategies are beneficial in enhancing reading comprehension and critical thinking skills, especially when adapted to vocational learners' context.